SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Quantifying sediment sources, pathways, and controls on fluvial transport dynamics on James Ross Island, Antarctica - Christopher D. Stringer; John F. Boyle; Filip Hrbáček; Kamil Láska; Ondřej Nedělčev; Jan Kavan; Michaela Kňažková; Jonathan L. Carrivick; Duncan J. Quincey; Daniel Nývlt (Journal of Hydrology, 2024)

Smallholder perceptions of land restoration activities: rewetting tropical peatland oil palm areas in Sumatra, Indonesia - Caroline Ward; Lindsay C. Stringer; Eleanor Warren-Thomas; Fahmuddin Agus; Merry Crowson; Keith Hamer; Bambang Hariyadi; Winda D. Kartika; Jennifer Lucey; Colin McClean; Neneng L. Nurida; Nathalie Petorelli; et al. (Regional Environmental Change, 2021)
The Indonesian government committed to restoring over 2 million ha of degraded peatland by the end of 2020, mainly to reduce peat fires and greenhouse gas emissions. Although it is unlikely the government will meet this target, restoration projects are still underway. One restoration strategy involves blocking peatland drainage canals, but the consequences of this for smallholder farmers whose livelihoods are dependent on agriculture are unclear. This paper investigates perceived impacts of canal blocks on smallholder farmers and identifies factors that affect their willingness to accept canal blocks on their land. We use data from 181 household questionnaires collected in 2018 across three villages in Jambi province, Sumatra. We found that the majority of respondents would accept canal blocks on their farms, perceiving that the blocks would have no impact on yields or farm access, and would decrease fire risk. Respondents who would not accept blocks on their farms were more likely to use canals to access their farms and perceive that canal blocks would decrease yields. The majority of farmers unwilling to accept canal blocks did not change their mind when provided with an option of a block that would allow boat travel. Our results improve understanding of why some smallholders may be unwilling to engage with peatland restoration. Further research is needed to understand the impact of canal blocks on smallholders’ yields. Engaging with stakeholders from the outset to understand farmers’ concerns, and perceptions is key if the government is to succeed in meeting its peatland restoration target and to ensure that the costs and benefits of restoration are evenly shared between local stakeholders and other actors.

Extracellular Vesicles Released by Glioblastoma Cells Stimulate Normal Astrocytes to Acquire a Tumor-Supportive Phenotype Via p53 and MYC Signaling Pathways - S. Hallal; D. M. Mallawaaratchy; H. Wei; S. Ebrahimkhani; B. W. Stringer; B. W. Day; A. W. Boyd; G. J. Guillemin; M. E. Buckland; Kimberley L. Kaufman (Molecular Neurobiology, 2019)

An Expandable Mechanopharmaceutical Device (2): Drug Induced Granulomas Maximize the Cargo Sequestering Capacity of Macrophages in the Liver - Phillip Rzeczycki; Gi Sang Yoon; Rahul K. Keswani; Sudha Sud; Jason Baik; Mikhail D. Murashov; Ingrid L. Bergin; Kathleen A. Stringer; Gus R. Rosania (Pharmaceutical Research, 2019)

An Exploration of Scenarios to Support Sustainable Land Management Using Integrated Environmental Socio-economic Models - L. Fleskens; D. Nainggolan; L. C. Stringer (Environmental Management, 2014)

Light brown apple moth (Epiphyas postvittana) (Lepidoptera: Tortricidae) colonization of California - D. M. Suckling; L. D. Stringer; D. B. Baird; R. C. Butler; T. E. S. Sullivan; D. R. Lance; G. S. Simmons (Biological Invasions, 2014)

Pheromone Disruption of Argentine Ant Trail Integrity - D. M. Suckling; R. W. Peck; L. M. Manning; L. D. Stringer; J. Cappadonna; A. M. El-Sayed (Journal of Chemical Ecology, 2008)

Towards zero-effluent pulp and paper production: The pivotal role of totally chlorine free bleaching - Paul A. Johnston; Ruth L. Stringer; David Santillo; Angela D. Stephenson; Irina Ph. Labounskaia; Hannah M. A. McCartney (Environmental Science and Pollution Research, 1997)